Guide to Peril Strait and Wrangell Narrows Alaska - Hopkins, William M., 1951- (University of Alaska Press, 2020)
"Learning how to pilot a ship through Wrangell Narrows and Peril Strait is not an easy matter for a vessel operator new to the area, or even for those with experience. It takes time, patience, and a certain appetite for risk. The older generation of captains knew the channels in great detail, but they did not write anything down to leave for the next generation coming up through the ranks. Recognizing the wealth of the knowledge these navigators possessed in their memories, William Hopkins decided to document their charts and methods as he himself learned to maneuver ships through these important and narrow southeastern Alaska channels. A now retired captian who logged many voyages, Hopkins delineates the navigable courses for passing these treacherous waterways in this essential guide."--